FREQUENCY OF LOWER LIMB INJURIES IN PROFESSIONAL SOCCER, RISK FACTORS AND CONSEQUENCES; A RETROSPECTIVE STUDY (Zdravstveni glasnik, 2024)
Introduction: There are many factors that can have an impact on the injury of soccer players. It is verydifficult to predict all factors, so turning to prevention, collecting data on injury patterns, and designing newstrategies for injury prevention among soccer players is extremely important.Objective: To determine the condition of lower limb injuries in football players of the Premier League ofBosnia and HerzegovinaMethods: Professional soccer players competing in the Premier League of Bosnia and Herzegovinaparticipated in a retrospective study. For this study, each soccer player filled out a questionnaire that wasnot standardized but was designed for the purposes of this research. Complaints about injuries during 2019were requested, as well as insight into types of injuries, methods of treatment, use of orthoses, bandages,and the like.Results: Out of a total of 129 subjects, 57.4 % had injuries, of which 50 had only one injury. Mostrespondents were injured during training (64.9 %), on normal surfaces (82.4 %). In 44.6 % of respondents,it was a non-contact, new injury, more often on the non-dominant leg, the most frequently injured weremuscles. 26 of them had an operation, and the recovery of the majority lasted up to 40 days.Conclusion: Exposure to various risk factors resulted in lower limb injuries in more than half of therespondents.